Picosecond lasers for tattoo removal: a systematic review. Issue 7 (September 2016) - Reiter, Ofer; Atzmony, Lihi; Akerman, Lehavit; Levi, Assi; Kershenovich, Ruben; Lapidoth, Moshe; Mimouni, Daniel
Abstract Given that the pigment particles in tattoos have a relaxation time of <10 ns, picosecond lasers would be expected to be more effective than nanosecond lasers in tattoo removal. To systematically review the evidence regarding the effectiveness and safety of picosecond lasers for tattoo removal, Pubmed, Cochrane Central Register of Controlled Trials (CENTRAL), ClinicalTrials.gov, and reference lists were searched for relevant trials. The primary outcome was >70 % clearance of tattoo pigment. Secondary outcomes were 90–100 % clearance of tattoo pigment, number of laser sessions required, and adverse effects. Eight trials were included, six with human participants (160 participants) and 2 with animal models. Seven of the eight trials explored the usage of either 755, 758, 795, 1064, or 1064/532-nm picosecond lasers for black and blue ink tattoos. In the human trials, 69–100 % of tattoos showed over 70 % clearance of pigment after 1–10 laser treatments. Reported side effects included pain, hyperpigmentation and hypopigmentation, blister formation and transient erythema, edema, and pinpoint bleeding. Included articles varied in type of laser investigated, mostly non-comparative studies and with a medium to high risk of bias. There is sparse evidence that picosecond lasers are more effective than their nanosecond counterparts for mainly black and blue ink tattoo removal, with minor side effects.